Long-term incidence of severe malaria following RTS, S/AS01 vaccination in children and infants in Africa: an open-label 3-year extension study of a phase 3 randomised controlled trial. Issue 8 (August 2019) - Tinto, Halidou; Otieno, Walter; Gesase, Samwel; Sorgho, Hermann; Otieno, Lucas; Liheluka, Edwin; Valéa, Innocent; Sing'oei, Valentine; Malabeja, Anangisye; Valia, Daniel; Wangwe, Anne; Gvozdenovic, Emilia; et al.
Summary: Background: Results from a previous phase 3 study showed efficacy of the RTS, S/AS01 vaccine against severe and clinical malaria in children (in 11 sites in Africa) during a 3–4-year follow-up. We aimed to investigate malaria incidence up to 7 years postvaccination in three of the sites of the initial study. Methods: In the initial phase 3 study, infants aged 6–12 weeks and children aged 5–17 months were randomly assigned (1:1:1) to receive four RTS, S/AS01 doses (four-dose group), three RTS, S/AS01 doses and a comparator dose (three-dose group), or four comparator doses (control group). In this open-label extension study in Korogwe (Tanzania), Kombewa (Kenya), and Nanoro (Burkina Faso), we assessed severe malaria incidences as the primary outcome for 3 additional years (January, 2014, to December, 2016), up to 6 years (younger children) or 7 years (older children) postprimary vaccination in the modified intention-to-treat population (ie, participants who received at least one dose of the study vaccine). As secondary outcomes, we evaluated clinical malaria incidences and serious adverse events. This trial is registered with ClinicalTrials.gov, number NCT02207816 . Findings: We enrolled 1739 older children (aged 5–7 years) and 1345 younger children (aged 3–5 years). During the 3-year extension, 66 severe malaria cases were reported, resulting in severe malaria incidence of 0·004 cases per person-years at risk (PPY; 95% CI 0–0·033) in the four-dose group, 0·007 PPY (0·001–0·052) in the three-dose group, and 0·009 PPY (0·001–0·066) in the control group in the older children category and a vaccine efficacy against severe malaria that did not contribute significantly to the overall efficacy (four-dose group 53·7% [95% CI −13·7 to 81·1], p=0·093; three-dose group 23·3% [–67·1 to 64·8], p=0·50). In younger children, severe malaria incidences were 0·007 PPY (0·001–0·058) in the four-dose group, 0·007 PPY (0·001–0·054) in the three-dose group, and 0·011 PPY (0·001–0·083) in the control group. Vaccine efficacy against severe malaria also did not contribute significantly to the overall efficacy (four-dose group 32·1% [–53·1 to 69·9], p=0·35; three-dose group 37·6% [–44·4 to 73·0], p=0·27). Malaria transmission was still occurring as evidenced by an incidence of clinical malaria ranging from 0·165 PPY to 3·124 PPY across all study groups and sites. In older children, clinical malaria incidence was 1·079 PPY (95% CI 0·152–7·662) in the four-dose group, 1·108 PPY (0·156–7·868) in the three-dose group, and 1·016 PPY (0·14–7·213) in the control group. In younger children, malaria incidence was 1·632 PPY (0·23–11·59), 1·563 PPY (0·22–11·104), and 1·686 PPY (0·237–11·974), respectively. In the older age category in Nanoro, clinical malaria incidence was higher in the four-dose (2·444 PPY; p=0·011) and three-dose (2·411 PPY; p=0·034) groups compared with the control group (1·998 PPY). Three cerebral malaria episodes and five meningitis cases, but no vaccine-related severe adverse events, were reported. Interpretation: Overall, severe malaria incidence was low in all groups, with no evidence of rebound in RTS, S/AS01 recipients, despite an increased incidence of clinical malaria in older children who received RTS, S/AS01 compared with the comparator group in Nanoro. No safety signal was identified. Funding: GlaxoSmithKline Biologicals SA.